Automated, technified and traditional aquaponic systems: a systematic review - Vaca Vargas, Sergio Alejandro; García Navarrete, Óscar Leonardo; Colorado Gómez, Mario Andrés (Ingeniería Solidaria, 2022)
Aquaponics are defined as hydroponic crops merged with recirculating aquaculture systems and bacteria, achieving a synergic relationship that takes fish wastewater and uses it in order to grow plants, then the last one in association with nitrifying bacteria are used as a natural filter that removes dissolved nitrogen, ammonia, among others, controlling the fish waste accumulation. Nowadays there are different research areas in aquaponics, from ones focused on the applied techniques in aquaculture and hydroponic sub-systems; through applied sciences such as modeling from both physical and chemical systems; arriving to the types of aquaponics, qualified from technification grades; concluding with fish and plant crop species and their interaction. In this paper a systematic review is carried out in order to observe the research current state in automated, technified and traditional aquaculture systems, thus having a sight of the investigative orientation in this field. This review is based on scientific papers from four databases, taken in March of 2020, obtaining 1356 results, evaluated and filtered for further analysis. From the review it was found that there is an exponential quantity growth in papers per year, moreover, it is noted that the paper fields of greatest concentration are aquaculture, agriculture, environment, water analysis, horticulture and electronics, the most worked species are lettuce (Lactuca sativa) in hydroponic NFT and tilapia (Oreochromis niloticus) in single recirculating aquaponic systems (SRAPS). With the obtained data it was built a diagram that consolidates current research branches in aquaponics.